At the Origins of the University Education System in Russia - Vasily N. Ponomarev (Высшее образование в России)
The article examines the history of the formation and development of University education in Russia during the reign of Alexander I. The author analyzes the key legislative acts and statutes of the Russian universities created in 1802–1805, as well as the reorganized in 1819 University of St. Petersburg. The article dwells on the history of Dorpat, Vilnius, Kharkiv, Kazan, and St. Petersburg Universities during the period of Alexander I’s reign. It is shown that as a result of the activities of the Emperor and his associates, a progressive harmonious system of education and higher education was created. The author traces how the educational policy began to change due to radically changed views of Alexander I in the last decade of his reign, which resulted in the clericalization of higher education, public education in general. The traditions initiated by M.V. Lomonosov were halted by the obscurantists and mystics. The universities were treated as hotbeds of freethinking, moral depravity, and philosophy was demonized as a source of spiritual contagion.